KONSEP PENDIDIKAN KARAKTER PERSPEKTIF ISLAM DAN IMPLEMENTASI DI SEKOLAH - Yunita, Yani (Al-Munqidz : Jurnal Kajian Keislaman, 2020)
Character education is a transformation of the values of life to be developed in a person's personality so that they become one in that person's life behavior. In this definition there are three important ideas, namely: 1) the process of transforming values, 2) being developed in personality, and 3) becoming one in behavior.Education has a very important role in shaping a person's character, because with education it can help someone who didn't know anything to know or is like a newborn if he is formed with a good education then he will be good and vice versa if he is formed. with a bad education then he will be a bad person too.In the Islamic perspective, theoretical character education has actually existed since Islam was revealed in the world as the Prophet Muhammad SAW was sent to improve or perfect human morals (character). Islamic teachings themselves contain a system of teachings that not only emphasize the aspects of faith, worship and mu'amalah, but also morals.